1985
DOI: 10.1111/j.1574-6968.1985.tb00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of ten distinct DNA fragments ofClostridium thermocellumcoding for cellulases

Abstract: Ten distinct Eco RI fragments of Clostridum thermocellum DNA have been cloned in Escherichia coli and shown to express enzymatic activities related to cellulose degradation. Two of the cloned fragments appeared to carry the previously characterized celA and celB genes, which code for the endoglucanases (EG) A and B. Five other cloned fragments code for hitherto unidentified EGs, which can be detected by the Congo red test for hydrolysis of carboxymethylcellulose (CMC). In addition, three separate clones hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Lamed et al (1983a) reported that at least eight components of the cellulosome display CMCase activity. The multiplicity of endoglucanases is evidenced by genetic analysis as well as biochemical studies, since seven different endoglucanase genes from C. thermocellum have been cloned (Cornet et al, 1983;Millet et al, 1985). An obvious question is why the organism produces so many different enzymes with seemingly the same activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamed et al (1983a) reported that at least eight components of the cellulosome display CMCase activity. The multiplicity of endoglucanases is evidenced by genetic analysis as well as biochemical studies, since seven different endoglucanase genes from C. thermocellum have been cloned (Cornet et al, 1983;Millet et al, 1985). An obvious question is why the organism produces so many different enzymes with seemingly the same activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another gene (celB) coding for another endoglucanase (endoglucanase B) has also been cloned in E. coli , and its gene product with a molecular weight of 66000 has been purified from E. coli (Beguin et al, 1983). Five additional genes coding for endoglucanases have also been cloned into E. coli (Millet et al, 1985). These five genes differ from one another and from cel A and CelB in their restriction maps.…”
mentioning
confidence: 99%
“…This paper describes the sequence of the celD gene, encoding endoglucanase D (EGD), one of the seven endoglucanase genes (EG) which were isolated by Millet et al from genomic banks of Clostridium thermocellum DNA (1).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable progress has also been made in the cloning and characterization of C. thermocellum cellulase genes (Beguin et al, 1983(Beguin et al, , 1986Cornet et al, 1983a, b;Millet et al, 1985;Grepinet & Beguin, 1986;Ha et al, 1987;Romaniec et al, 1987a, b;Schwarz et al, 1987Schwarz et al, , 1988Soutschek-Bauer & Staudenbauer, 1987;Babykin et al, 1988;Grabnitz & Staudenbauer, 1988;Hazelwood et al, 1988;Mann, 1988;Piruzyan et al, 1988). The most thoroughly characterized cloned gene product to date is the endoglucanase D (EGD).…”
Section: Clostridiummentioning
confidence: 99%